Pharmacokinetic interaction between mitotane and etoposide in adrenal carcinoma: a pilot study. Issue 12 (December 2018) - Jouinot, Anne; Royer, Bernard; Chatelut, Etienne; Moeung, Sotheara; Assié, Guillaume; Thomas-Schoemann, Audrey; Bertherat, Jérôme; Goldwasser, François; Blanchet, Benoit
Abstract : Background: The combination of mitotane and platinum-etoposide chemotherapy is a front-line treatment in metastatic adrenocortical carcinoma (ACC), although this regimen shows limited efficacy. Pharmacokinetic drug–drug interaction between mitotane, a strong CYP3A4 inducer, and etoposide, which is a substrate of CYP3A4, may contribute to chemoresistance. The aim of this pilot study was to assess the pharmacokinetic interaction between mitotane and etoposide in ACC patients. Methods: Five consecutive ACC patients treated with platinum etoposide (120–150 mg/m 2 day 1–2–3 at cycle 1), with or without concomitant mitotane, were included. In the absence of limiting toxicity, a dose escalation of etoposide was proposed since cycle 2. Plasma etoposide concentrations were measured using liquid chromatography at 0, 4 and 24 h after each infusion. Clearance and area under the curve (AUC) of etoposide were determined at each cycle. Results: Patients received two to six chemotherapy cycles, in association with mitotane ( N = 4) or after mitotane discontinuation ( N = 1). Etoposide clearance was two-fold higher with concomitant mitotane (4.95 L/h) than after mitotane discontinuation (2.53 L/h, P = 0.014), and 2.5-fold higher than that in reference population not treated with mitotane (1.81 L/h). Etoposide dose escalation was performed in four patients under mitotane, resulting in two minor tumor responses and one severe toxicity (febrile aplasia) at dose of 300 mg/m 2 /day. Tumor response was associated with higher etoposide AUC (267.3 vs 188.8 mg.h/L, P = 0.04). Conclusion: A drug–drug interaction between mitotane and etoposide may contribute to the low efficacy of platinum-etoposide chemotherapy. This pilot study suggests further a potential benefit of increasing etoposide dose in ACC patients receiving mitotane.